Rationalizing convergence and developments on the internet - Kevin Shepherdson. (2010)
The aims of the study are to: a) Demonstrate a symbiotic relationship between Internet and existing media. By looking at the Internet from the perspective of existing media (the World Wide Web as an extension of media). b) Account for the Convergence of Mass Media, Telecommunications and Computing industries on the Internet by looking at how communication and information flow in these industries. c) Study the Internet from a media perspective. This study devised a model of analysis called the Information Dissemination Model that examined the process of information dissemination in various media to better understand the Internet as an information and communication medium. The proposed model involved looking at three stages of the information dissemination process. They are: Content Creation, Content Delivery and Content Reception. Using this model, the study was able to analyse all the media using a common framework.